HMGB1–RAGE signaling pathway in severe preeclampsia. Issue 10 (October 2015) - Zhu, Linlin; Zhang, Zhan; Zhang, Linlin; Shi, Ying; Qi, Jiahui; Chang, Aimin; Gao, Junjun; Feng, Yang; Yang, Xiaoqian
Abstract Introduction Placental dysfunction and increased inflammation are believed to underlie the pathogenesis of severe preeclampsia (PE). High-mobility group box 1 (HMGB1), a recently identified inflammatory cytokine, has been known to contribute to the development of inflammatory responses in PE. This study intends to elucidate the mechanisms of HMGB1–RAGE signaling pathway in the pathogenesis of PE. Methods The mRNA levels of relative gene of HMGB1 pathway, HMGB1, RAGE and NF-κB p65, were analyzed by real-time PCR in placentas collected from 61 normotensive pregnant women and 64 women with severe PE. Additionally, levels of HMGB1 and RAGE protein were detected in frozen placental specimens by western blot, and the locations of them were evaluated in the well-characterized tissue microarray by immunohistochemistry. ELISA was further used to detect HMGB1 level in maternal serum. Results Compared with matched control placentas, the mRNA levels of HMGB1, RAGE and NF-κB p65 were increased in severe preeclamptic placentas. In severe preeclamptic placentas, HMGB1 and RAGE immunoreactivity were increased in the cytoplasm of trophoblast cells. Western blot was employed to further confirm that RAGE protein level was elevated significantly in severe PE group. In addition, there was an increased level of HMGB1 in the maternal serum of severe PE group. Discussion HMGB1 nuclear-cytoplasmic translocation may induce the binding of HMGB1 to its receptors, consequently, intrigue NF-κB activity in severe PE. HMGB1–RAGE signaling pathway may be involved in the pathogenesis of PE.